MAKANAN HALAL DAN MAKANAN HARAM DALAM PERSPEKTIF FIKIH MUAMALAH - M. Rikwan ES M. Rikwan ES (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Understanding and the need for sharia provisions regarding halal, haram, and doubtful based on the Qur'an and Hadith as well as the opinions of the jurists are very important and become a guide for consumers and producers in producing halal products. Halal assurance guidelines in Indonesia are implemented in the halal assurance system. Every halal product that is circulated by the producer must be accountable to the product. From the explanation above, it can be concluded that halal and thayyib food are all forms of food that are permitted by syara' law to consume them and contain nutritional elements for the health of the human body. Humans are very dependent on the food they eat, if halal and thayyib food is consumed, it will have a good effect on the health of the body. On the other hand, if you eat bad food, it will not be good for your health. And there are many verses of the Qur'an that explain the command to consume halal and thayyib food.